Gatemonium: A Voltage-Tunable Fluxonium - William M. Strickland; Bassel Heiba Elfeky; Lukas Baker; Andrea Maiani; Jaewoo Lee; Ido Levy; Jacob Issokson; Andrei Vrajitoarea; Javad Shabani (PRX Quantum)
We present a new style of fluxonium qubit, gatemonium, based on an all-superconductor-semiconductor hybrid platform. The linear inductance is achieved using 600 planar Al-InAs Josephson junctions (JJs) in series. By tuning the single junction with a gate voltage, we demonstrate electrostatic control of the effective Josephson energy, tuning the weight of the fictitious phase particle. One- and two-tone spectroscopy of the gatemonium transitions further reveal details of the hybrid plasmon-fluxon spectrum. Accounting for the nonsinusoidal current-phase relation of the single junction, we fit the measured spectra to extract charging and inductive energies. We conduct time-domain characterization of the plasmon modes and find that energy-relaxation times are limited by inductive loss, possibly in the thin aluminum film. We discuss future directions for this platform in gate-voltage-tunable high-plasma-frequency enhanced-impedance junction arrays, and enhanced coherence times for voltage-tunable architectures.